EXPOSURE OF YOUNG ANIMALS TO NUTRITIVE AND NON- NUTRITIVE SWEETENERS AND THEIR METABOLIC EFFECTS IN ADULTHOOD (Arquivos do Mudi, 2023)
Sucralose (SCL) is one of the most widely used edulcorants in the world, including bychildren and adolescents, but its effects on metabolic programming are not sufficient andconclusive. In this study we evaluated whether ingestion of SCL or sucrose (SUC) by youngrats interferes with metabolic parameters in the adult rat. We used 21-day-old male wistarrats, which received pure water (control) or water added SUC or SCL, until 60 days of age.When they reached 90 days of age, half of the animals were fed a high fat diet (HFD). Theanimals were euthanized at 120 days of age. When fed only the standard diet, SUC intake inthe young phase caused significant (p<0,05; ANOVA) increase in body weight (11%),adiposity (48%), insulinemia (53%) and insulin resistance (56%) and reduced lipolyticresponse to adrenergic stimulation (53%) in the adult animal. When fed the HFD diet, bothsweeteners causing significant (p<0,05; ANOVA) increases in adiposity (SUC=32%;SCL=36%) and liver fat (SUC=34%; SCL=41%), with increased insulinemia (75%) only inthe SLC group. We conclude that adding SUC and SCL to the diet during youth may increasethe risks of obesity, insulin resistance and hepatic steatosis in adulthood and accentuate themetabolic disturbances caused by HFD diets.